I wish someone had told me ... : the best advice for building a great career and a meaningful life - Perino, Dana (Fox News Books, 2025)
"... A blueprint for success in your life and career. An all-star line-up of Dana's lifelong friends and Fox News personalities with wide-ranging talents and accomplishments share amazing stories about their own experiences, offering invaluable guidance and wisdom on a range of subjects ..."--